Studies on the variability of Anagrus atomus (L.) (Hymenoptera Mymaridae) and on a similar species living on bramble (Bollettino di zoologia agraria e bachicoltura, 2024)
The species Anagrus atomus (L.) is redescribed. with particular attention to intraspecific variability.A biometric study has allowed to separate A. atomus from a new form living on Edwardsiana rosae L. on bramble and rose.New diagnostic characters are given and a new synonymy is proposed.